2020
DOI: 10.1038/s41598-020-69186-6
|View full text |Cite
|
Sign up to set email alerts
|

A robust and miniaturized screening platform to study natural products affecting metabolism and survival in Caenorhabditis elegans

Abstract: In this study a robust, whole organism screening based on Caenorhabditis elegans is presented for the discovery of natural products (NP) with beneficial effects against obesity and age-related diseases. Several parameters of the elaborated workflow were optimized to be adapted for probing multicomponent mixtures combining knowledge from traditional medicine and np chemistry by generating optimized small-scale extracts considering scarcity of the natural source, solubility issues, and potential assay interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 95 publications
0
48
0
Order By: Relevance
“…Both organisms were obtained from the Caenorhabditis Genetics Center (University of Minnesota). Details of the miniaturized Nile red assay in C. elegans including the composition of all media and reagents have been published recently [21]. Briefly, hermaphrodite animals were maintained on nematode growth medium (NGM) agar plates seeded with 20 µg of OP50 at 16 • C as described by Stiernagle [36].…”
Section: Nile Red Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Both organisms were obtained from the Caenorhabditis Genetics Center (University of Minnesota). Details of the miniaturized Nile red assay in C. elegans including the composition of all media and reagents have been published recently [21]. Briefly, hermaphrodite animals were maintained on nematode growth medium (NGM) agar plates seeded with 20 µg of OP50 at 16 • C as described by Stiernagle [36].…”
Section: Nile Red Assaymentioning
confidence: 99%
“…The applicability of the presented method was outlined using positive controls fluoxetine and 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) as an application example in [21]. Fluoxetine (F-132) and AICAR (A9978) were obtained from Sigma Aldrich with a purity of ≥98%.…”
Section: Experimental Validation Nile Red Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Tannin-rich extracts were further subjected to tannin depletion to avoid any unspecific assay interferences. Protocols for the generation of tannin-depleted samples have been described previously [12,13] and successfully applied in several studies [11,[14][15][16]. For this process, the dried CH 2 Cl 2 -MeOH extracts were restored in 4-mL MeOH, loaded onto a 3-mL solid-phase extraction cartridge (Phenomenex, Torrance, CA, USA; AH0-7001) filled with polyamide gel (Carl Roth, Karlsruhe, Germany; CC-6; 900 mg) and washed two times with MeOH.…”
Section: Preparation Of Herbal/fungal Extractsmentioning
confidence: 99%
“…Recent studies also suggest the possibility of GJF as an anti-obesity agent. For instance, Park et al reported that the ethanol extract of GJF inhibited adipogenesis in white-induced 3T3-L1 cells [ 15 ], and Zwirchmayr et al showed that methylene chloride and methanol extracts of GJF reduced lipid accumulation in Caenorhabditis elegans [ 16 ]. However, whether GJF has an effect on non-shivering thermogenesis (NTS) is unknown.…”
Section: Introductionmentioning
confidence: 99%